Development of the Petroleum Refining in the Republic of CÃ´te D’ivoire- Primary Processing of Refining - Adiko, Serge-B.; R.A, Kemalov (International Journal of Engineering and Technology, 2018)
The article is considering the technology of primary processing of S. I. R (Societe Ivoirienne de Raffinage). General modern technology of petroleum refiningThe problems with primary processing technologies of refining and ability development of the petroleum refining in the Republic of CÃ´te d'Ivoire. Comparison of the two types of technologies (primary of refining) between SIR for Cote dâ€™ivoire and general technology in Russia.S. I. R (Societe Ivoirienne de Raffinage) is the only petroleum refinery in the Republic of ivory coastThe Republic of CÃ´te d'ivoire is located in West Africa with a population of 22.8 million (data for 2014 b is the second economic power in sub-region (West Africa) after Nigeria, with an average of 8% of GDP over the last five years, Economic development of the country and its economic development is related to petroleum production and refining in the Republic of CÃ´te d'ivoire.Refining is the obvious economic rate for a more diversified and more competitive economyÂ Â